Evaluasi Kecernaan In Sacco Beberapa Pakan Serat yang Berasal dari Limbah Pertanian dengan Amoniasi - Andayani, Jul (Fakultas Peternakan Universitas Jambi, 2008)
The aim of this study was to evaluate the effect ammoniated feed from agriculture by products on the in sacco dry matter, organic matter and crude protein digestibilities. This study was assigned into a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were different types of low quality fibre of agricultural by-products found in Jambi Province; A = ammoniated rice straw with 6 % of urea and 15 % of inoculated rumen digesta, B = ammoniated palm oil fibre with 6% of urea and 15 % of inoculated rumen digesta, C = ammoniated corn peel with 6 % of urea and 15 % of inoculated rumen digesta, D = ammoniated top cane with 6 % of urea and 15 % of inoculated rumen digesta. Result of this study showed that the treatments were significantly affect (P<0,05) on the dry matter, organic matter and crude protein degradations. Ammoniation significantly increased degradation of feed compared with those without ammoniation. It is concluded that ammoniation with urea and addition of rumen digesta increased fibre quality of agricultural by-products. Different of type of ammoniated feed resulted in the difference respond on the nutrient degradation.